A 3D-to-2D Transform Algorithm for Incorporating 3D Antenna Radiation Patterns in SCM - Kanj, H.; Lusina, P.; Ali, S.M.; Kohandani, F. (IEEE antennas and wireless propagation letters, 2009)
We present a method to incorporate the effect of the three-dimensional (3D) antenna radiation patterns into a two-dimensional (2D) multiple-inputmultiple-output (MIMO) channel model. The proposed method is a low-complexity technique that increases the accuracy of existing 2D spatial channel model (SCM) proposed by 3GPP for performance analysis of long-term evolution (LTE) MIMO. Using a realistic 3D antenna field pattern and the 2D 3GPP SCM, the 3D-to-2D transform algorithm (3D-2D-TF) gives a 5% outage capacity within 0.5 b/s/Hz when compared to a higher complexity averaging approach using 18-cut planes (18-CP) of the 3D radiation pattern. This is achieved with 6% of the run-time complexity. By not including the elevation information, the original SCM 2D model gives an outage capacity prediction error of up to 2.4 b/s/Hz as compared to the 18-CP averaging approach. The 3D-2D-TF is therefore a promising low-complexity candidate that increases the accuracy of 2D channel models for MIMO 4G performance evaluations.